FROM THE FORMULA “TO THE GLORY OF GOD THE FATHER” (PHILIPPIANS 2:11) TO THE FORGOTTEN THEOLOGY OF PHIL 2:6-11 AS PAULINE FORMULA FOR MONOTHEISM: Part II - Ayeni, Ayodele (Science et Esprit)

(untitled) (Collège universitaire dominicain, Ottawa, 2022)
Taking into consideration the number of times God appears in Phil 2:5/6-11, compared with Christ – 4 to 2, one wonders why Phil 2:5/6-11 is called “Carmen Christi.” Also, a clear theology becomes very manifest, when one looks at the whole letter, and a neglected monotheism gapes past scholarly commentaries on Philippians. The “Fatherhood” of God towards humanity extends to Jesus as well, while alluding to a monotheistic creed in Phil 2:11.